Interaction between internal shear reinforcement and external FRP systems of RC beams: Experimental study - Teo, W. (Bentham Science Publishers B.V., 2017)
Extensive research effort has been conducted on the shear strengthening of reinforced concrete (RC) beams with externally bonded FRP systems. However, there are still few aspects on their behaviour that are yet to be fully understood. One of them is the effect of shear interaction between internal transverse shear reinforcement and the external FRP systems. This paper is intended to study experimentally the interaction between these two shear reinforcement components. To do so, a total of five concrete beams were assembled in this investigation. All beams were properly instrumented in order to obtain as much data as possible. Four beams were externally strengthened with FRP with different strengthening and wrapping schemes. Their influence and interaction with the internal transverse stirrups in shear resistance were discussed based on the modes of failure exhibited, deflection and strain (steel and FRP) responses. Overall the results obtained are in good agreement with many researches which indicated that addition of externally bonded FRP, as a matter of fact, preserves the integrity of internal transverse stirrups. With continuous FRP sheets and U-wrapped scheme, greater FRP contribution to the shear resistance can be expected. © 2017 Teo et al.